Hubungan intensitas kebisingan dan pencahayaan sinar las dengan gangguan kesehatan pada pekerja bengkel las di Kota Banda Aceh - Syahrizal Syahrizal; Junaidi Junaidi; Nasrullah Nasrullah (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Noise is unwanted sound or noise because it disturbs or arises against the will of the person concerned. The recommended noise threshold value is 85 dB at 8 hours of working time. Humans need lighting to recognize objects that affect vision: the eyes, nerves, and the visual nerve center of the brain. When noise is above the threshold value of lighting (300 Lux), this can lead to health problems or potential occupational hazards.Objectives: The study aims to determine the relationship between noise intensity and welding light illumination and health problems in Banda Aceh City welding workshop workers.Methods: Observational research with a cross-sectional design was conducted in Banda Aceh City in 2021. The sample was 30 welding workshop workers in 6 different places. Data collection was carried out by interview using a questionnaire, observation through a checklist, and interview. Data processing was done in stages: editing, coding, entry, and cleaning data—statistical analysis using the Chi-square test at a 95% confidence level.Results: The study's results on the noise variable due to work obtained a p-value= 0,330, so there is no relationship between noise and health problems in welding workshop workers (p> 0,05). While the lighting variable caused by welding obtained a p-value= 1,000, this also does not show a relationship between lighting (welding light) with health problems of welding workshop workers (p> 0,05) in Banda Aceh City.Conclusion: Noise intensity and lighting (welding light) have no association with health problems among welding workshop workers in Banda Aceh city. However, workers must follow SOPs and pay attention to PPE (Personal Protective Equipment) to prevent health problems and avoid work accidents.